2000
DOI: 10.1093/ajcn/72.2.355
|View full text |Cite
|
Sign up to set email alerts
|

A paradoxical increase in resting energy expenditure in malnourished patients near death: the king penguin syndrome

Abstract: In malnourished persons near death, there is an increase in REE and in protein catabolism. The reason for this increase is unknown but could relate to consumption of the last mobilizable muscle mass and to diseased cellular membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 22 publications
2
69
0
1
Order By: Relevance
“…40 -42 It has been indicated that albumin levels remain virtually unchanged under conditions of severe protein-energy malnutrition in otherwise healthy individuals until near terminal starvation. 43 In addition, to be used as a nutritional marker, albumin is well established as a strong predictor of outcome in dialysis patients. 44,45 Furthermore, Rocco et al 46 recently showed that failure to meet the treatment goal recommended by the National Kidney Foundation of albumin levels Ͼ40 g/L is associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…40 -42 It has been indicated that albumin levels remain virtually unchanged under conditions of severe protein-energy malnutrition in otherwise healthy individuals until near terminal starvation. 43 In addition, to be used as a nutritional marker, albumin is well established as a strong predictor of outcome in dialysis patients. 44,45 Furthermore, Rocco et al 46 recently showed that failure to meet the treatment goal recommended by the National Kidney Foundation of albumin levels Ͼ40 g/L is associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…33 These patients maintain serum albumin levels in the normal range, even when BMIs reach the low teens. [33][34][35][36] Only when health status approaches death does serum albumin actually fall. 34 Additional insights are gleaned from the Minnesota Experiment.…”
Section: Serum Albumin and Malnutrition In The General Populationmentioning
confidence: 99%
“…[33][34][35][36] Only when health status approaches death does serum albumin actually fall. 34 Additional insights are gleaned from the Minnesota Experiment. 37 Initiated in the early 1940s by Ancel Keys, this seminal study explored the biology and physiology of human starvation.…”
Section: Serum Albumin and Malnutrition In The General Populationmentioning
confidence: 99%
“…Although protein calorie malnutrition alone may be associated with hypoalbuminemia, in otherwise healthy individuals, serum albumin concentration does not decline until starvation is preterminal (64). Albumin concentration decreases in dialysis patients primarily as a consequence of increased inflammation with a subsequent decline in the rate of albumin synthesis (62) coupled with a failure to downregulate albumin catabolism as occurs during protein restriction.…”
Section: Hypoalbuminemiamentioning
confidence: 99%